Natural Product Derived Nano-Formulation for the Enhancement of Antimalarial Properties in Alpinia galanga - Sam, Jian Hung (Curtin University, 2024)
This research focuses on combatting malaria with local plants. As such, galangal was extracted via supercritical CO2 and formulated into nanoemulsion with extracts from betel leaf. The results showed that the nanoemulsion formulation gave higher antimalarial properties with reduced cytotoxicity. In a nutshell, the end product showed immense potential as an antimalarial supplemental aid and as a candidate for further research as an antimalarial drug.